2020
DOI: 10.1038/s41467-020-20001-w
|View full text |Cite
|
Sign up to set email alerts
|

A human tissue map of 5-hydroxymethylcytosines exhibits tissue specificity through gene and enhancer modulation

Abstract: DNA 5-hydroxymethylcytosine (5hmC) modification is known to be associated with gene transcription and frequently used as a mark to investigate dynamic DNA methylation conversion during mammalian development and in human diseases. However, the lack of genome-wide 5hmC profiles in different human tissue types impedes drawing generalized conclusions about how 5hmC is implicated in transcription activity and tissue specificity. To meet this need, we describe the development of a 5hmC tissue map by characterizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 40 publications
7
93
0
Order By: Relevance
“…Unlike 5mC which is recognized for its role in repressing not only protein-coding genes but also a vast amount of transposons in the human genome 6 , 5hmC modifications are associated with active gene regulation 7 . A recent study of a 5hmC map of human tissues showed that 5hmC is enriched preferentially in tissue-specific gene bodies and enhancers 8 , representing a distinct genome-wide distribution from 5mC. Global and focal differential 5hmC modifications have been observed in several cancers, including hematological malignancies 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike 5mC which is recognized for its role in repressing not only protein-coding genes but also a vast amount of transposons in the human genome 6 , 5hmC modifications are associated with active gene regulation 7 . A recent study of a 5hmC map of human tissues showed that 5hmC is enriched preferentially in tissue-specific gene bodies and enhancers 8 , representing a distinct genome-wide distribution from 5mC. Global and focal differential 5hmC modifications have been observed in several cancers, including hematological malignancies 9 .…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate 5hmC global changes, we then illustrated 5hmC distributions along gene bodies (± 3 kb), which were similar to those of human adults 17,25 (Fig. 1c).…”
Section: Resultsmentioning
confidence: 95%
“…This phenomenon depends on TET3 activity and the de ciency of zygotic DNMT3A and DNMT1 24 . Although the regulatory power and plasticity of 5hmC have been revealed in human adults 20,25 , its function and reprogramming are still unclear during human foetal organ development after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…In some of them, we observe the opposite process [ 86 ]. In addition, the methylation level of both individual genes and the general level is tissue and individually specific [ 95 , 96 , 97 ]. The progress in the study of the dependence of the methylation degree of specific loci in the genome on the chronological and biological variation allows for the assumption that in the future it will be possible to develop models predicting the life expectancy and biological age of a human based on the methylation degree of specific loci in selected tissues [ 98 , 99 , 100 , 101 ].…”
Section: Organismal Ageingmentioning
confidence: 99%